Fracture resistance and failure modes of endodontically-treated permanent teeth restored with Ribbond posts vs other post systems: a systematic review and meta-analysis of in vitro studies - Meghana Aditya Vartak; Vibha Rahul Hegde; Sanitra Rahul Hegde; Ushaina Fanibunda (Restorative Dentistry & Endodontics)
Objectives This systematic review aimed to investigate the fracture resistance and mode of failure of endodontically-treated permanent teeth restored with Ribbond posts (Ribbond, Inc.) compared with endodontically-treated permanent teeth restored with other post systems. Methods A comprehensive, systematic literature search was carried out using several electronic databases: MEDLINE/PubMed, Google Scholar, and Cochrane Library. Two separate researchers were appointed to identify the studies meeting the eligibility criteria, and to perform the data extraction, risk of bias, and quality assessment. Results Twelve studies were included in the quantitative analysis. Meta-analysis was performed with 11 of the 12 included articles. The meta-analysis showed that Ribbond posts have a fracture strength less than prefabricated metal posts, cast metal posts, and prefabricated fiber posts and greater than custom e-glass fiber posts. Mode of failure analysis revealed that Ribbond posts have the most favorable non-catastrophic fractures. Conclusions Although Ribbond posts have lower fracture resistance, their favorable mode of failure makes them potentially the most biomimetic post system.